A Peer Helping Program for the Middle School - Henriksen, Eleanor M. (Canadian Journal of Counselling and Psychotherapy, 2011)
A peer helping program was implemented at Central Middle School in Dawson Creek in the school year 1989-1990 following a school evaluation. This article describes the implementation of the program and its evaluation. The evaluation of the program included pre and post-training surveys of the trainees and an untrained comparison group on the acquisition of helping skills, personal development, and changes in self-concept, as well as surveys of parents, of the teaching staff, and the student body. Program evaluation methods and results are presented, and recommendations are made based on the evaluation.